2018
DOI: 10.1039/c8nr02623h
|View full text |Cite
|
Sign up to set email alerts
|

Versatile cyclodextrin nanotube synthesis with functional anchors for efficient ion channel formation: design, characterization and ion conductance

Abstract: Biomimetic ion channels with different materials have been extensively designed to study the dynamics in a confined medium. These channels allow the development of several applications, such as ultra-fast sequencing and biomarker detection. When considering their synthesis, the use of cheap, non-cytotoxic and readily available materials is an increasing priority. Cyclodextrins, in supramolecular architectures, are widely utilized for pharmaceutical and biotechnological applications. Recent work has shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 130 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…CDNTs with controlled lengths, diameters, and number of cyclodextrins and selective chemical modifications were used as ion nanochannels and inserted into lipid bilayers to transport ions. [107,108] As shown by the I-V curves of the CDNTs (Figure 4C), their conductance was found to be 0.077 ± 0.005 nS. [108] In addition, a COF F I G U R E  Representative 1D nanochannel-structured organic membranes.…”
Section:  D Nanochannel-structured Membranesmentioning
confidence: 95%
See 1 more Smart Citation
“…CDNTs with controlled lengths, diameters, and number of cyclodextrins and selective chemical modifications were used as ion nanochannels and inserted into lipid bilayers to transport ions. [107,108] As shown by the I-V curves of the CDNTs (Figure 4C), their conductance was found to be 0.077 ± 0.005 nS. [108] In addition, a COF F I G U R E  Representative 1D nanochannel-structured organic membranes.…”
Section:  D Nanochannel-structured Membranesmentioning
confidence: 95%
“…CDNTs with controlled lengths, diameters, and number of cyclodextrins and selective chemical modifications were used as ion nanochannels and inserted into lipid bilayers to transport ions. [ 107,108 ] As shown by the I – V curves of the CDNTs (Figure 4C), their conductance was found to be 0.077 ± 0.005 nS. [ 108 ] In addition, a COF with oligo(ethylene oxide) chains exhibited enhanced lithium‐ion transport through a vehicle mechanism in contrast to a COF without oligo(ethylene oxide) chains on the ordered 1D nanochannel walls (Figure 4D), [ 109 ] which provides new inspiration for developing ion conductors.…”
Section: Nanochannel‐structured Membranesmentioning
confidence: 99%
“…It has been shown that cyclodextrin-based channels can insert into biological membranes and exhibit ion transport activity without causing any cytotoxicity . Alpha, beta, and gamma cyclodextrins are all capable of forming ion channels, with the current through the channel increasing linearly with externally applied voltage. , A detailed picture of the ion transport mechanism through these cyclodextrin channels and how the alpha, beta, and gamma cyclodextrin channels respond to permeation of different ions, however, are not understood.…”
Section: Introductionmentioning
confidence: 99%
“…At first, the protein channels were the main sensors used to perform numerous studies 7-9 . Thanks to material science, chemistry, nanoscience and molecular biology, it is now possible to design and manufacture new classes of nanopores: solid-state sensors 10,11 , DNA origami nanopores 12,13 , carbon 14,15 or cyclodextrin nanotubes [16][17][18] , hybrid nanopores 19-21 and glass 22,23 or quartz nanopores 24 with DNA aptamers 25 . The increased interest in nanopore research has been mainly associated to the ultra-fast DNA sequencing challenge, recently achieved by Oxford Nanopore Technology [26][27][28][29] .…”
mentioning
confidence: 99%
“…Nanopore technology has become a sensitive, selective, low cost, label-free, real-time, and transportable tool for sensing a wide variety of molecules, including ions, polymers, polyelectrolytes, viruses, ligand–molecule complexes, and biomolecules. It allows for the analysis of transport properties, conformations, folding, size, sequence, or chemical modifications. At first, the protein channels were the main sensors used to perform numerous studies. Thanks to material science, chemistry, nanoscience, and molecular biology, it is now possible to design and manufacture new classes of nanopores: solid-state sensors, , DNA origami nanopores, , carbon , or cyclodextrin nanotubes, hybrid nanopores, and glass , or quartz nanopores with DNA aptamers . The increased interest in nanopore research has been mainly associated with the ultrafast DNA sequencing challenge, recently achieved by Oxford Nanopore Technology. The objectives at the horizon of this field comprise proteomic sequencing, , biomarker detection (of micro-RNAs as well as infinitesimal peptides and proteins quantities), and single-molecule mass spectrometry. , Up to now, the best sensitivity for biotechnological or heath applications is obtained through biological channels.…”
mentioning
confidence: 99%